The Monocyte to High‐Density Lipoprotein Cholesterol Ratio in the Prediction for Atherosclerosis: A Retrospective Study in Adult Chinese Participants. Issue 1 (7th September 2020) - Zhou, Yaqing; Wang, Liyi; Jia, Limei; Lu, Baojin; Gu, Guoqiang; Bai, Long; Cui, Wei
Abstract: The ratio of monocyte to high‐density lipoprotein cholesterol level (MHR) was a newly proposed inflammatory and oxidative stress marker. This study aimed to explore the association between MHR and Brachial‐ankle pulse wave velocity (Ba‐PWV) in adult Chinese participants. A total of 2029 participants were divided into two groups according to the Ba‐PWV: a high Ba‐PWV group (Ba‐PWV ≥1400 cm/s) and a low Ba‐PWV group (Ba‐PWV < 1400 cm/s). According to the cut‐off points of quartile of MHR, the participants were divided into four groups. The relationship between MHR and Ba‐PWV was analyzed. After adjusting for potential confounders, a non‐linear relationship between MHR and Ba‐PWV was found in the participants, and the inflection point was 7.78 in the non‐linear curve. On the left of the inflection point, MHR had a positive correlation with Ba‐PWV (OR = 1.17, 95% confidence interval (CI): 1.08 to 1.28, p  < 0.01). However, there was no obvious relationship between MHR and Ba‐PWV on the right of the inflection point (OR = 0.96, 95% CI: 0.90 to 1.01, p = 0.117). Further demographic analysis demonstrated that the positive relationship between MHR and Ba‐PWV was found in the female participants with hypertension family history, but without a current history of hypertension, smoking, or drinking ( p  < 0.05). An increased MHR is a risk factor of atherosclerosis, which may predict the potential development of atherosclerosis. When the MHR is close to 7.78, it has the highest predictive value for the risk of atherosclerosis occurrence.